Minority Shareholder Monitoring and German Corporate Governance Empirical Evidence and Value Effects - Thamm, Christian; Thamm, Christian (Peter Lang, 2013)
This book comprises three studies on minority shareholder monitoring in Germany. Mandatory disclosure requirements have increased transparency. An analysis of the information that is publicly available is presented, regardless of the size of the target corporation. The second essay in the form of an event study pays special attention to the German supervisory board and its appointment for a fixed term. Capital markets perceive an activist effort as being more credible under certain circumstances. The study as a whole is empirical evidence for increased minority shareholder activity in Germany. The evidence presented supports the strong shareholder rights perspective. It conflicts with the weak shareholder rights view brought forward in the international literature.